Further investigation of confirmed urinary tract infection (UTI) in children under five years: a systematic review - Cooper Julie; Whiting Penny F; Westwood Marie E; Watt Ian S; Kleijnen Jos (BMC, 2005)
Abstract Background Further investigation of confirmed UTI in children aims to prevent renal scarring and future complications. Methods We conducted a systematic review to determine the most effective approach to the further investigation of confirmed urinary tract infection (UTI) in children under five years of age. Results 73 studies were included. Many studies had methodological limitations or were poorly reported. Effectiveness of further investigations: One study found that routine imaging did not lead to a reduction in recurrent UTIs or renal scarring. Diagnostic accuracy: The studies do not support the use of less invasive tests such as ultrasound as an alternative to renal scintigraphy, either to rule out infection of the upper urinary tract (LR- = 0.57, 95%CI: 0.47, 0.68) and thus to exclude patients from further investigation or to detect renal scarring (LR+ = 3.5, 95% CI: 2.5, 4.8). None of the tests investigated can accurately predict the development of renal scarring. The available evidence supports the consideration of contrast-enhanced ultrasound techniques for detecting vesico-ureteric reflux (VUR), as an alternative to micturating cystourethrography (MCUG) (LR+ = 14.1, 95% CI: 9.5, 20.8; LR- = 0.20, 95%CI: 0.13, 0.29); these techniques have the advantage of not requiring exposure to ionising radiation. Conclusion There is no evidence to support the clinical effectiveness of routine investigation of children with confirmed UTI. Primary research on the effectiveness, in terms of improved patient outcome, of testing at all stages in the investigation of confirmed urinary tract infection is urgently required.